Gambling Preferences, Options Markets, and Volatility - Blau, Benjamin M.; Bowles, T. Boone; Whitby, Ryan J. (Journal of Financial and Quantitative Analysis, 2016)
This study examines whether the gambling behavior of investors affects volume and volatility in financial markets. Focusing on the options market, we find that the ratio of call option volume relative to total option volume is greatest for stocks with return distributions that resemble lotteries. Consistent with the theoretical predictions of Stein (1987), we demonstrate that gambling-motivated trading in the options market influences future spot price volatility. These results not only identify a link between lottery preferences in the stock market and the options market, but they also suggest that lottery preferences can lead to destabilized stock prices.